Hypertonic perfusion reduced myocardial injury during subsequent ischemia and reperfusion in normal and hypertensive rats - Chen Li-Bing; Liu Tao; Wu Jing-Xiang; Chen Xiao-Feng; Wang Li; Fan Chun-Lin; Gao Ping-Jin; Higashino Hideaki; Lee Wen-Hsiung; Yuan Wen-Jun; Chen Hong (Acta Pharmacologica Sinica, 2016)
AIM: To determine the effects of hypertonic solution on myocardial ischemia and reperfusion injury in normal and stroke-prone hypertensive rat hearts in vitro. METHODS: Hearts were perfused in an isolated-perfused Langendorff apparatus and perfused with normal or hypertonic solution (360 mOsm/L, by addition of NaCl to the normal perfusate of 300 mOsm/L) before subjected to 30 min ischemia followed by 40 min isotonic reperfusion. Heart function, myocardial creatine kinase leakage, norepinephrine release, and ventricular calcium content were determined. RESULTS: Normal rat hearts with hypertonic perfusion showed higher recovery rate of spontaneous beating than control hearts after ischemia. Hypertensive rat hearts perfused with hypertonic solution also had better recovery in diastolic function and less creatine kinase leakage than hypertensive controls. Concomitantly, myocardial release of norepinephrine was also reduced from hypertensive hearts perfused with hypertonic solution. There was no significant difference in myocardial calcium content between normal and hypertonic perfused hypertensive hearts. CONCLUSION: Hypertonic perfusion may precondition the hearts and protect them from ischemia and reperfusion injury in both normal and hypertensive rats. The modulation of hypertonic perfusion on myocardial norepinephrine release and its role in cardioprotection needs further investigation.